2019
DOI: 10.1016/j.hpb.2019.03.360
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of liver transplantation or resection after transarterial radioembolization with Yttrium-90 for unresectable hepatocellular carcinoma

Abstract: Background: The benefit of transarterial radioembolization (TARE) in patients with unresectable hepatocellular carcinoma (HCC) is increasingly evidenced. However, data on outcome of liver transplantation or resection after TARE remain scarce. This study aimed to assess the safety and feasibility of surgery after TARE in patients with unresectable HCC. Methods: Patients exclusively undergoing TARE followed by either orthotopic liver transplantation (OLT) or liver resection (LR) for HCC between 2012 and 2016 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…29 Our data and that of others only further supports that TARE should not be viewed as a palliative treatment for advanced liver disease, but rather an opportunity to reexamine a patient's response to treatment for evaluation of another course of action. 11,18 Our review of the current literature shows that TARE followed by hepatectomy can be safe and effective for certain patients, and we hope our study spurs further investigation into the factors that determine what makes a patient have a safer hepatectomy. In the future, we hope to study prognostic factors of adverse events through collaboration with other institutions.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…29 Our data and that of others only further supports that TARE should not be viewed as a palliative treatment for advanced liver disease, but rather an opportunity to reexamine a patient's response to treatment for evaluation of another course of action. 11,18 Our review of the current literature shows that TARE followed by hepatectomy can be safe and effective for certain patients, and we hope our study spurs further investigation into the factors that determine what makes a patient have a safer hepatectomy. In the future, we hope to study prognostic factors of adverse events through collaboration with other institutions.…”
mentioning
confidence: 79%
“…7,8 To date, there is a dearth of studies reporting the outcomes of patients who receive a hepatectomy following TARE. [8][9][10][11][12][13][14][15][16][17][18][19] The few published studies have reported a wide range of major complication frequency (16%-78%) 13,19 questioning the true safety of this treatment paradigm. Furthermore, there are other discrepancies in the literature regarding the frequency of certain common morbid events, including bile leak (0%-45%).…”
mentioning
confidence: 99%
“…Initial results of this approach were included in a recent report about the use of radioembolisation prior to transplant or resection. 56 Inhibition of the immune checkpoint programmed cell death protein 1 and its ligand (PD-1/ PD-L1) has been shown to produce major, longlasting responses in approximately 20% of patients with advanced HCC. 57 In lung cancer, where PD-L1 expression is linked to response, the response rates among PD-L1+ patients with advanced disease was 27%.…”
Section: Key Pointmentioning
confidence: 99%
“…LR after radioembolisation for initially unresectable HCC also showed interesting survival results, without increasing perioperative complication rates, in patients at various BCLC stages. 173 , 174 Moreover, radioembolisation was also associated with atrophy of the treated lobe and hypertrophy of the future liver remnant, thus facilitating LR. Some authors even suggest a higher rate of patients successfully downstaged compared to TACE, with longer time to disease progression.…”
Section: Overcoming Old Barriersmentioning
confidence: 99%